Strategi Pengembangan Kampung Wisata Berbasis Kearifan Lokal di Desa Mirat Kabupaten Majalengka - Sumiarsa, Fitri; Kiky Yustikasari; Evi Novianti (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
Mirat Village is a village in Leuwimunding District, Majalengka Regency, West Java. It is one of the villages with the potential to become a tourist destination. Using local culture as a foundation, this study aims to describe the development strategy of a tourist village in Mirat Village, Majalengka Regency. To achieve these objectives, data collection is conducted through observation and a literature review of various journals, and the resulting data is analyzed descriptively and qualitatively. Upon data analysis, five categories were identified, including attraction, accessibility, public facilities, community empowerment, and marketing or promotion. The results of the research revealed that Mirat Village only meets two of the five tourist village criteria, namely tourist attraction and community empowerment, while the other three criteria are still hindered.